Internal Conflict of the Main Character in Frozen (2013) - Ni Made Melisa Damayanti; Luh Putu Laksminy; Gek Wulan Novi Utami (Peneliti.net, 2026)
This study aims to analyze the internal conflict experienced by the main character Elsa in the film Frozen (2013). The theory use to analize the conflict from Kanney (1966), specifically the category of Man vs. Self. The method used to collect the data is a qualitative approach with a document analysis study design. Data were obtained from dialogues, scenes, and song lyrics in the film that reflect Elsa's inner turmoil. The analysis results show that Elsa experiences conflict between fear and the desire to be free, between self-identity and social expectations, as well as between guilt and the need for emotional closeness. These conflicts play a crucial role in Elsa's character development and convey a universal message about self-acceptance and the courage to face fear.